Revaluating the Tanzi-Model to Estimate the Underground Economy - J. Ferwerda; I. Deleanu; Brigitte Unger (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2010)
Since the early 1980s, the interest in the nature and size of the non-measured economy (both the informal and the illegal one) was born among researchers in the US. Since then, several models to estimate the shadow and/or the underground economy appeared in the literature, each with its own theoretical pros and cons. In this paper we show that it is possible to overcome earlier expressed criticism of the Tanzi-model (1983). Its lack of a base year without any underground economy can be overcome, by using the natural experiment of the introduction of the Euro. However, this paper also comes up with new criticism. It shows that the crucial relationship of the Tanzi-model between taxes and the demand for cash money is not time robust, hence the model is not useful for estimating the underground economy nowadays. We believe that the change in financial conditions could partially explain the decline in the relevance of taxes as a means to evaluate the underground economy. We build a revised Tanzi model and try to find variables apart from tax evasion incentives in order to explain the underground economy.
Keywords: 330; Underground Economy Estimation; Shadow Economy; Tax Evasion